Market Clearing Method for Regional Coordinated Transaction Scheduling with Reserve Ancillary Services Sharing - Shuo LIU; Menghan ZHANG; Songtai YU; Mingxu XIANG; Zhifang YANG (Zhongguo dianli)
To achieve the targets of carbon peak and carbon neutrality with the increasing utilization of renewables, regional coordinated transaction scheduling has emerged as a promising approach that can deliver complementary economic advantages across regions while promoting renewable energy consumption. However, market clearing of reserve ancillary services sharing between different regions remains a challenging problem. This paper proposes a method for building the tie-line feasible region with joint consideration of power energy and reserve ancillary services, and develops a market clearing model for regional coordinated transaction scheduling with reserve ancillary services sharing. The proposed model explicitly incorporates reserve ancillary services sharing constraints and sculpts the energy-reserve transaction feasible region. Based on the feasible regions, the market clearing method provides for synchronous energy-reserve transactions through tie-line transmission. A case study of an interconnected network demonstrates that the proposed method can achieve reserve ancillary services sharing across different regions, promote renewable energy accommodation, and reduce total operating costs.